Dead-end lives : drugs and violence in the city shadows - Briggs, Daniel (Criminologist); Gamero, Rubén Monge (Policy Press, 2017)
Julia nervously emerges from her shabby tent in the suburban wastelands on the outskirts of Madrid to face another day of survival in one of Europe's most problematic ghettos: she is homeless, wanted by the police, and addicted to heroin and cocaine. She is also five months pregnant and rarely makes contact with support services. Welcome to the city shadows in Valdemingómez: a lawless landscape of drugs and violence where the third world meets the Wild West. Briggs and Monge entered this area with only their patience, some cigarettes and a mobile phone and collected vivid testimonies and images of Julia and others like her who live there. This important book documents what they found, locating these people's stories and situations in a political, economic and social context of spatial inequality and oppressive mechanisms of social control--